A Synthetic Discrete Design Methodology of High-Frequency Isolated Bidirectional DC/DC Converter for Grid-Connected Battery Energy Storage System Using Advanced Components - Zhao, Biao; Song, Qiang; Liu, Wenhua; Sun, Yandong (IEEE transactions on industrial electronics (1982), 2014)
This paper reviews recent advances of key components in isolated bidirectional dc-dc converter (IBDC) and discusses potential of IBDC based on advanced components. The concept of safe operation area of IBDC is proposed and clearly defined, which is determined by the intersection of the effective operation areas of transmission power, current stress, and current root mean square. By analyzing efficiency and power density characteristic, this paper points out that the efficiency optimization of IBDC needs to give way to the power density optimization. On this basis, a novel synthetic discrete optimization design methodology of IBDC based on advanced components for battery energy storage system (BESS) is proposed. Finally, an experimental prototype is implemented, and some design suggestions for hardware optimization are provided. The experimental results verify the effectiveness of the designed BESS and show that the practical applications of next-generation high-frequency conversion system are expected with the appearance and application of advanced components.